EVALUATION THE CORROSION PROTECTION OF STRUCTURES BY ACTUAL CONDITION (Collection of scientific works «Modern structures of metal and wood», 2022)
This work includes the results of studies about the state of the secondary protection against  corrosion  to  ensure  the  building  metal  structures’  durability.  The  task  of  preserving  the qualitative and quantitative indicators under the influence of the aggressive atmosphere in industrial enterprises is being solved. Methodology. The technique of improving the efficiency of the means technology and methods of metal structures secondary protection from corrosion during the technical condition  monitoring  is  stated.  Results.  The  developed  diagnostic  procedures  include  statistical accounting  and  the  corrosion  state  monitoring  of  metal  structures,  identifying  the  causes  of  the occurred defects and damage. The basis of prediction for service life and reaching the limit states are determined by the level of vulnerability and threats, taking into account the actual state. Scientific novelty.  A procedure  for  servicing  structures based  on  the  actual  state  has been  developed.  The procedure for drawing up specifications of corrosion protection measures according to the criterion of corrosion hazard has been determined. It makes possible to meet the requirements for the reliability of  building  metal  structures,  to  prescribe  technological  safety  management  measures  during  the established service life of construction objects.  Practical significance. The proposed  generalized indicators of the actual structures’ corrosion state determine the structure’s operability as a whole. The  functional  dependencies  between  the  operability  of  the  main  and  auxiliary  structures  are established.  The  relationship  between  the  values  of  corrosion  resistance  indicators  and  metal structures durability are determined. Actual technical condition control consists of checking that the values of these indicators are within acceptable limits. Taking into account the degree of operating environment  aggressiveness  is  one  of  the  determining  factors  in  order  to  ensure  the  secondary protection effectiveness against corrosion. This procedure is the basis for the rational specifications appointment  for  anti-corrosion  protection  systems  with  subsequent  display  in  the  design  and technological documentation.